2019
DOI: 10.1186/s12874-019-0708-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the importance of key risk factors in predicting chronic bronchitic symptoms using a machine learning approach

Abstract: Background Chronic respiratory symptoms involving bronchitis, cough and phlegm in children are underappreciated but pose a significant public health burden. Efforts for prevention and management could be supported by an understanding of the relative importance of determinants, including environmental exposures. Thus, we aim to develop a prediction model for bronchitic symptoms. Methods Schoolchildren from the population-based southern California Children’s Health Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The lower MSE value is, the better. The result of this study was supported by previous research comparing the performance between gradient boosting machine and random forest [15,16].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The lower MSE value is, the better. The result of this study was supported by previous research comparing the performance between gradient boosting machine and random forest [15,16].…”
Section: Resultssupporting
confidence: 78%
“…The approach evaluated here, using random forest and gradient boosting machine has rarely been used in tobacco plantation except in the health sectors such as predicting chronic bronchitis symptom analysis [15], smoking behaviour [16] and tobacco spending in each household in Georgia [17]. All previous studies using gradient boosting machine showed that the method could provide an excellent performance in predicting and classifying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…XGB and GB algorithms are the most complex algorithms, and therefore, they are thought to have the best predictive power. LR algorithms are less computationally intensive than DT, RF, XGB, and GB algorithms; however, this often comes at the expense of accuracy and predictability [10][11][12][13]. The five algorithms were used to predict patient LOS for the posterior patients with the Sci-Kit Learn package in Python (National Institute for Research in Computer Science and Automation, Rocquencourt, France) [14].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, there is evidence to suggest that ML methods are already beginning to be (mis)used in this manner. [39][40][41] Integration of modern causal inference methods into ML applications should be sought and encouraged for answering causal questions. Indeed, there is already promising research being done in this area (e.g.…”
Section: Lessons For Machine Learningmentioning
confidence: 99%